Effectiveness of aspirin in preventing deep vein thrombosis following proximal femoral fracture surgery in Japan - Takao Ohmori; Kazukiyo Toda; Takuya Taoka; Takeshi Ishihara; Yasuo Ito (Scientific Reports)
Abstract Previous studies have shown that aspirin is effective as a prophylactic agent against venous thromboembolism (VTE) following proximal femoral fractures (PFF). In Japan, there is a lack of evidence regarding its efficacy and safety in this context. Consequently, aspirin is not covered by insurance for the prevention of venous thrombosis. This study aimed to investigate whether continued aspirin use in patients with PFF, who were already taking aspirin for cerebrovascular disease prevention before injury is effective as a prophylaxis for deep vein thrombosis (DVT). We retrospectively analyzed PFF patients (≥ 65 years) who underwent postoperative duplex ultrasonography from January 2010 to December 2023.The study compared patients taking aspirin alone (aspirin group) and those not taking antiplatelet agents or anticoagulants (control group), matched by propensity scores. We enrolled 1064 patients while 161 (15%) were in the aspirin group. After matching, 128 patients were analyzed. DVT incidence was not statistically significant between the aspirin (54) and control groups (60) (OR: 0.81; 95%CI: 0.49- 1.36; p = 0.44). Proximal DVT incidence was also similar (OR: 2; 95%CI: 0.50–7.00; p = 0.33). Additionally, since use of other postoperative antithrombotic prophylaxis (78%) is thought to have a significant impact on the incidence of DVT, a subgroup analysis was conducted to evaluate the effect of aspirin in patients who did not receive postoperative antithrombotic prophylaxis. Similarly, there was no statistically significant difference in either DVT (OR: 1.38; 95% CI: 0.55–3.42; p = 0.49) or proximal DVT (OR: 2.00; 95% CI: 0.37–10.92; p = 0.42). This study demonstrates that aspirin is not effective for preventing VTE in patients with PFF in Japan.